(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Disclosure of artificial intelligence (AI) is one of the new developments in the business environment and has begun to play a prominent role in all fields, especially in the accounting field, as (AI) has become an integral part of business operations and is crucial for banks that care about the requirements of modern technology. The research aims to measure the level of disclosure of artificial intelligence systems in annual reports on performance indicators. To achieve this goal, a sample of (10) private banks listed on the Iraq Stock Exchange was selected for the purpose of conducting an applied study by analyzing the content of the financial reports of those banks for the period (2018 - 2023). Disclosure of artificial intelligence was measured by developing a list of indicators indicating (AI), while the performance of banks was evaluated by three indicators: (ROA) (ROE), (TD/TL). Descriptive and inferential statistical methods were also used in the program (SPSS) to analyze the collected data and test the research hypotheses. The research concluded that there is a positive and significant impact of disclosure of artificial intelligence on the performance evaluation indicators of Iraqi banks according to the first indicator (ROA) and the second indicator (ROE). The study recommends setting clear standards for disclosing the use of artificial intelligence in banks and training employees on how to use AI and how to disclose it in financial reports.